Synthesis and Characterization of Ag/Ce1-xMnxO2-δ Oxidation Catalysts - David Alami; Viktor Bulavin (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
The aim of this work was to obtain samples of Ag - doped manganese-cerium mixed oxides and explore their characteristics. Six catalysts were prepared by the co-precipitation process followed by impregnation method for Ag incorporation. These catalysts were characterized in particular by means of TEM, XRD, TPR and examined on the reaction of hydrogen peroxide catalytic decomposition. The samples obtained were solid solution nanoparticle agglomerates with irregular surface morphology. The results pointed out that the highest activity in oxidation reactions should possess Ag/Ce0.23Mn0.77O2-δ catalyst. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)